Using ontology to mine and classify Li-Fraumeni Syndrom patients - Budaruiche, Ricardo Moura Sekeff (2014)
The Li-Fraumeni Syndrome (LFS) is a syndrome that causes multiple primary tumors in children and young adults. The main motivation of this work is to create a single integrated system that allows doctors and researchers from the A.C. Camargo Cancer Center to relate family histories, clinical and molecular data present in di erent databases through an innovative data integration methodology in order to improve the existing LFS diagnose criteria, or even to propose a new set of clinical criteria. (Párrafo extraído del texto a modo de resumen)